Signals and systems : continuous and discrete - Ziemer, Rodger E (Pearson education, 2001)
Signals and systems : continuous and discrete / Ziemer, Rodger E.. -- Delhi: Pearson education, 2001 621.3815 Z65 4th ed. No. of Copies : 1